A mathematical model to predict the performance of desiccant coated evaporators and condensers. (January 2020) - Hua, L.J.; Ge, T.S.; Wang, R.Z.
Abstract: Desiccant coated heat exchangers (DCHEs), utilizing an inner cooling source to remove sorption heat, are promising alternatives for evaporators and condensers (DCEs/DCCs) in vapor compression (VC) heat pumps. A mathematical model is necessary to facilitate the design, analysis and performance prediction of the component and the relevant systems. In this study, a three-dimensional model of DCEs/DCCs is proposed, accounting for the two-phase phenomena, the periodical switchover, the solid-side resistance, the fluid transport in multiple directions and the coupled heat and mass transfer. Study reveals that, high latent load (inlet humidity) reduces the sensible heat handling capacity of the DCEs, while the dehumidification capacity is almost independent of its sensible heat load. DCEs possess a satisfying effect of dehumidification above the dew point, thus it is unnecessary to employ low evaporation temperature. Meanwhile, the adsorption-desorption temperature difference of 30 °C seems to be the optimal value for the commonly adopted evaporation temperatures (10 °C-20 °C). For a specific coating thickness, there is a critical switchover period where the best performance of dehumidification is obtained. Switchover period shorter than the critical time should be avoided, and elongating the switchover cycle helps balance the ability of the system to handle the sensible and latent heat loads at the same time.